Islamic Character Building through Positive Education PERMA Model in MI Nurul Hidayah Samarinda - Ubaidillah, Faruk; Afandi, Nur Kholik (Edudeena : Journal of Islamic Religious Education, 2024)
This research aims to describe the process of implementing the PERMA Model of Positive Education in forming the Islamic character of students at Madrasah Ibtidaiyah Nurul Hidayah Samarinda. This research uses a qualitative approach with a case study method. Research subjects included teachers, students and madrasa heads. Data collection was carried out through observation, in-depth interviews and documentation. The data analysis technique uses an interactive model with three stages: data reduction, data processing and concluding. The research results show that implementing the PERMA Model of Positive Education at MI Nurul Hidayah has succeeded in creating a positive learning environment and increasing students' learning motivation so that, in the end, it can form a better Islamic character for students. This can be implemented through Positive Emotions, Engagement, Relationship, Meaning and Accomplishment.